(untitled) (Journal of Contemporary Studies, 2013)
Abstract The security relations of states have always been conducted and observed through a realist lens, i.e. power politics, military alliances or competitions. The last two decades have changed dimensions of state politics in a profound way. The phenomena of globalization and war on terror with subsequent shifts in economic relations among states of different region are bound to have effect on Chinese security policy as well. This paper aims to understand the nexus between questions of traditional and non-traditional security in Chinese policy of cooperation. The regional relationship of China with its neighbours has been contentious and reserve in past. However, since the 1990s, the dynamics of socio-economic and political environment in East Asia is also changing. It is thus necessary to analyze regional and bilateral security cooperation of China comprehensively. This paper therefore explains it evaluates policy coordination through bilateral and multilateral channels against the background of overall security political relationship.